Penguatan Strategi Branding Berbasis Digital dan Etika Islam pada Madrasah Swasta melalui Pelatihan Pemasaran Pendidikan - Halimatuzzahrah Halimatuzzahrah; Patriana Aulia; Khoeriyah Khoeriyah (Ngarsa: Journal of Dedication Based on Local Wisdom, 2025)
This community service was conducted using qualitative methods, including observations and interviews, within community service-based learning (service learning), which integrated community service activities with reflective learning throughout the mentoring process. The training materials focused on strengthening institutional identity, utilizing social media as a means of public communication, developing educational promotional content, and applying Islamic ethical values in madrasah branding activities. The results of the community service activity showed an increase in participants' understanding and skills in managing madrasahs' images in a more planned and sustainable manner. Partner madrasahs began implementing more consistent digital communication strategies, improving the quality of published content, and paying attention to the principles of honesty, politeness, and responsibility in conveying information to the public. The initial implications of this activity are seen in the increased visibility of madrasahs in digital media and the strengthening of madrasahs' image as professional and ethical Islamic educational institutions.Keywords: Branding Strategy, Digitalisation, Islamic Ethics, Service Learning. Pengabdian kepada masyarakat ini dilaksanakan dengan menggunakan metode kualitatif melalui observasi dan wawancara dalam kerangka pembelajaran berbasis pengabdian kepada masyarakat (service learning) yang mengintegrasikan kegiatan pengabdian dengan proses pembelajaran reflektif selama proses pendampingan berlangsung. Materi pelatihan difokuskan pada penguatan identitas kelembagaan, pemanfaatan media sosial sebagai sarana komunikasi publik, pengembangan konten promosi pendidikan, serta penerapan nilai-nilai etika Islam dalam kegiatan branding madrasah. Hasil kegiatan pengabdian menunjukkan adanya peningkatan pemahaman dan keterampilan peserta dalam mengelola citra madrasah secara lebih terencana dan berkelanjutan. Madrasah mitra mulai menerapkan strategi komunikasi digital yang lebih konsisten, meningkatkan kualitas konten yang dipublikasikan, serta memperhatikan prinsip kejujuran, kesantunan, dan tanggung jawab dalam menyampaikan informasi kepada masyarakat. Implikasi awal dari kegiatan ini terlihat pada meningkatnya visibilitas madrasah di media digital serta semakin kuatnya citra madrasah sebagai lembaga pendidikan Islam yang profesional dan beretika.Kata kunci: Strategi Branding, Digitalisasi, Etika Islam, Service Learning.